Handbook of simulation and financial risk management with practical case studies - Chan, Ngai Hang.; Wong, Hoi Ying, 1974- (Hoboken : Wiley, 2013)
This authoritative handbook illustrates practical implementation of simulation techniques in the banking and financial industries through use of real-world, time-sensitive applications. Striking a balance between theory and practice, it demonstrates how simulation algorithms can be used to solve practical problems and showcases how accuracy and efficiency in implementing various simulation methods can be used as indispensable tools in risk management. It also covers topics such as volatility, fixed-income derivatives, LIBOR Market Models, risk measures, and includes over two-dozen recognized s.
List of figures -- List of tables -- Preface -- An introduction to excel vba -- Background -- Structured products -- Volatility modeling -- Fixed-income derivatives I : short-rate models -- Fixed-income derivatives II : libor market models -- Credit derivatives and counterparty credit risk -- Value-at-risk and related risk measures -- The Greeks -- Appendix -- References -- Subject index -- Author index.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Finance -- Simulation methods; Risk management -- Simulation methods; BUSINESS & ECONOMICS -- Investments & Securities -- General; Risk management - Simulation methods; Electronic books; Electronic books